Health System Creation and Integration at a Health Sciences University: A Five-Year Follow-up. Issue 6 (November 2017) - Slade, Catherine P.; Azziz, Ricardo; Levin, Steven; Caughman, Gretchen B.; Hefner, David S.; Halbur, Kimberly V.; Tingen, Martha S.; James, Susan
Abstract : EXECUTIVE SUMMARY: Shifting healthcare market forces and regulation have exerted near-constant pressure on U.S. academic health centers (AHCs) attempting to successfully execute their traditional tripartite mission. A governance structure and organizational alignment that works well under one set of conditions is rarely optimal when conditions change. Thus, the degree and type of alignment of an AHC's clinical, educational, and faculty practice organizations have changed regularly within the sector, typically landing near one end or the other on a continuum from fully aligned with centralized governance to largely independent with separate governance. The authors examine the case of Georgia Regents University and Health System in this context. In step with industry trends, the institution's governance structure swung from fully aligned/centralized governance in the early 1990s to essentially separate and decentralized by 2000. In 2010, the Georgia Regents University organizations achieved rapid realignment by creating a governance structure of sufficient strength and flexibility to absorb and adjust to continuing external upheaval. The hospitals, clinics, and physician–faculty practice group were combined into one integrated health system, then aligned with the university to form the state's only public AHC under aligned, but distinct, corporate and management structures. The years since reorganization have seen significant growth in patient volumes and complexity, improved service quality, and enhanced faculty physician satisfaction, while also significantly increasing economic contributions from the health system to the academic mission. This case study offers observations and lessons learned that may be useful to other higher education institutions considering reorganization.